2015
DOI: 10.1002/poc.3447
|View full text |Cite
|
Sign up to set email alerts
|

Reaction ofOHradical and ozone with methyl salicylate – aDFTstudy

Abstract: A theoretical study on the reaction mechanism of methyl salicylate (MeSA), a green leaf volatile organic compound with OH radical and ozone, has been carried out using density functional theory methods using B3LYP, M06-2X and MPW1K functionals with 6-311++G(d,p) basis set. The atmospheric degradation pathways of MeSA with OH radical are studied under two different pathways, viz. H-atom abstraction and electrophilic addition of OH radical. The hydrogen abstraction from -OH group is found to be the dominant reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
11
1
Order By: Relevance
“…As shown in Table , this reaction channel is exothermic and exergonic with ΔrH298o = –11.21 kcal mol –1 and ΔrG298o = –13.85 kcal mol –1 at the B3LYP level of theory. From the earlier studies , it is well observed that early transition state exhibits exothermic nature of the reaction. Pathway 2: H‐atom abstraction from theCH 3 group in α position with respect to the carbonyl group . The H‐atom abstraction from the –CH 3 group in α position with respect to the carbonyl group proceeds through transition state TS2 to form a product complex (PC2).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in Table , this reaction channel is exothermic and exergonic with ΔrH298o = –11.21 kcal mol –1 and ΔrG298o = –13.85 kcal mol –1 at the B3LYP level of theory. From the earlier studies , it is well observed that early transition state exhibits exothermic nature of the reaction. Pathway 2: H‐atom abstraction from theCH 3 group in α position with respect to the carbonyl group . The H‐atom abstraction from the –CH 3 group in α position with respect to the carbonyl group proceeds through transition state TS2 to form a product complex (PC2).…”
Section: Resultsmentioning
confidence: 96%
“…As shown in Table III, this reaction channel is exothermic and exergonic with r H o 298 = -11.21 kcal mol -1 and r G o 298 = -13.85 kcal mol -1 at the B3LYP level of theory. From the earlier studies [37,38], it is well observed that early transition state exhibits exothermic nature of the reaction. 898Å.…”
Section: the Three Rc And Pc Have Both O-h•••o And C-h•••o Hydrogenmentioning
confidence: 99%
“…However, the 3 (C3) and 6 (C6) positions have individual VdW structure, shown as VdW2 and VdW4, respectively. Although Priya et al [20] . investigated the oxidation reaction of MeSa by OH radical previously at several levels of theory and reported the different barrier height for each level, but they did not report the formation of VdW complexes for the different positions of MeSa ring during the oxidation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…As far as we know, the only theoretical study of the reaction of MeSa with atmospheric oxidants of OH and O 3 in the gas phase was performed by Priya et al [20] . who reported the para position as the most probable position with largest branching ratio due to its shallow potential.…”
Section: Introductionmentioning
confidence: 99%
“…M06-2X/aug-cc-pVTZ level of theory was chosen for the stationary point geometry optimization and frequency calculations, which is believed that the extra exchange-correlation functional included for accurate thermochemical and kinetical calculations especially [24]. This method has been identified by a couple of relevant gas phase radical oxidation reactions [25] [26]. Furthermore, the intrinsic reaction coordinates (IRC) approach calculations were carried out at the same level in order to verify the designed transition structures connecting to the expected energy minima.…”
Section: Methodsmentioning
confidence: 99%